Strengthening Recovery in Central and Eastern Europe : EU11 Regular Economic Report - World Bank (Washington, DC, 2014)
Economic growth is expected to almost double in EU11 (Estonia, Latvia, and Lithuania, the Czech Republic, Hungary, Poland, the Slovak Republic, Bulgaria, Croatia, Romania and Slovenia) in 2014, and continue to strengthen in 2015. The northern countries of Estonia, Latvia, Lithuania will continue to be amongst the fastest growing countries in the EU, despite the negative impact of falling external demand as growth slows in their main trading partners. Croatia is the only country expected to remain in recession, for a sixth consecutive year, in 2014, as declining domestic demand continues to outweigh export growth. Recovery is expected to be gradual, with growth not reaching pre-crisis rates for some time. Inflation rates are expected to remain below targets during 2014, with some countries already experiencing deflation, but as global commodity prices stabilize, activity increases and output gaps diminish, inflation is expected to gradually rise. Fiscal consolidation will continue in 2014 and 2015, but at a more gradual pace than in the previous years. Economic growth forecasts in the EU11 are subject to multiple risks, mainly on the downside, as the global financial situation remains fragile. Rising global interest rates coupled with volatile capital markets, or an extended period of regional geopolitical tensions could slow the European recovery and constrain exports, credit and investment in EU11. While labor market conditions have started to improve, the pace of job creation and reduction in unemployment rates are likely to be gradual. Many of the economies in the EU11 face the twin challenge of high youth unemployment and rapidly aging populations. EU11 countries also struggle with equipping the next generation with the skills necessary to achieve their full potential e.g. in literacy, math and science. The persistence of large numbers of inactive and unemployed youth therefore poses unique risks of creating a "lost generation" of workers. Understanding the cyclical and structural nature of youth unemployment is therefore important to mitigate the potentially damaging cycle between youth unemployment and broader economic growth and productivity.